Effervescent Granule Formulation of Purple Sweet Potato Leaf Extract (Ipomoea batatas L.) Antin 3 Variety As an Antioxidant Nutraceutical: Formulasi Granul Effervescent Ekstrak Daun Ubi Jalar Ungu (Ipomoea batatas L.) Varietas Antin 3 Sebagai Nutraceutical Antioksidan - Damaranie Dipahayu (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Antin 3 variety of purple sweet potato (Ipomoea batatas L.) leaf extract contains flavonoids and polyphenols as antioxidants so that have the potential to be used as nutraceuticals. Effervescent granules have acidic and basic components which can react with water to form CO2 so that it can covering the taste of extract and is able to give a fresh taste. There are two formulas with different types of binders, namely PVP K30 5% (F1) and CMC Na 1.5% (F2). The granulation method used is wet granulation. The effervescent granule tests carried out were organoleptic, particle size distribution, flow rate, angle of repose, Hausner's ratio, compressibility index, dispersion time test, foam height, moisture content, pH and hedonic test. The evaluation results obtained were that F1 and F2 did not have significant differences in the values of moisture content, Hausner's ratio and compressibility index. F1 and F2 had significant differences in the values of flow rate, pH and dispersibility time. F1 had the hedonic test results ( color, aroma and taste) which were more preferable. F1 had dispersibility time and foam height values which did not meet the requirements while F2 meets the requirements.